Zeptogram Mass Detection Using Triple Walled Carbon Nanotubes - T. Patel, Minesh; M. Patel, Ajay; Y. Joshi, Anand (Current Nanoscience, 2017)
Background: The aim of this paper is to use triple walled carbon nanotubes (TWCNT) as a sensor and explore the effect of change in the length of outer and middle tubes keeping smaller tubes length constant. Methods: In this paper continuum models of TWCNTs are used, with the finite element procedure to evaluate the resonance frequencies of TWCNT. TWCNTs are treated as a number of concentric elastic cylindrical layers of SWCNTs. The interlayer interaction is described by the Van der Waals potential. The Van der Waals force field between the interfacial layers is represented by a spring element. Fixed free TWCNTs and bridged TWCNTs having attached mass at the end of their outer wall and at the center of the outer wall respectively have been analyzed with the variation in the mass. Result: Fundamental frequencies in TWCNT resonators are in GHz which is much less than those of the DWCNT and/or SWCNT resonator in THz, because of the increasing inter tube interference. TWCNT resonators model was simulated and a decrease in the frequencies with decrease in length ratios was observed. Also, an increase in frequency shift is observed with an increase in the length ratio for different values of attached mass. Conclusion: TWCNTs with different length variations can sense a mass up to zeptogram. TWCNTs with different wall lengths have been used for mass sensor may serve as a component in digital communication.
Keywords: Vibration